2019
DOI: 10.1002/anie.201900549
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Intramolecular Rotation To Enhance Two‐photon Imaging of Aβ Plaques through Minimizing Background Fluorescence

Abstract: The aggregation of amyloid beta (Ab)p roteins in senile plaques is ac ritical event during the development of Alzheimersdisease,and the postmortem detection of Ab-rich proteinaceous deposits through fluorescent staining remains one of the most robust diagnostic tools.I na nimal models, fluorescence imaging can be employed to follow the progression of the disease,and among the different imaging methods, two-photon microscopy(TPM) has emerged as one of the most powerful. To date,s everal near-infrared-emissive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 28 publications
(19 reference statements)
0
49
0
Order By: Relevance
“…For most hydrophobic fluorescence probes (for nonactivatable probes), the restricted conformation of a probe and the hydrophobicity of the residing environment of the probe have strong influence on the turn-on effect of fluorescence 31 , 43 , 65 67 . Similarly, this principle can be applied to chemiluminescence probes.…”
Section: Discussionmentioning
confidence: 99%
“…For most hydrophobic fluorescence probes (for nonactivatable probes), the restricted conformation of a probe and the hydrophobicity of the residing environment of the probe have strong influence on the turn-on effect of fluorescence 31 , 43 , 65 67 . Similarly, this principle can be applied to chemiluminescence probes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our research team has focused on the development of a naphthalene-based donor (D)-acceptor (A) type of dipolar fluorescent dyes and its applications for the detection of metal ions, enzyme activity, amino acid, cell sub-organelles, disease biomarkers, and carcinogens [20,21,22,23,24,25]. During the research process, we found a fast hydrazone-formation between D-A type naphthaldehyde and hydrazine by o -MOM assistant, and we utilized this property in developing a fluorescent probe, HyP-1 [18] .…”
Section: Resultsmentioning
confidence: 99%
“…Probe 61 could label Aβ plaques in the frontal cortex of 5xFAD‐Tg mice with good BBB penetration and excellent two‐photon cross‐sections. [ 50 ]…”
Section: Alzheimer's Diseasementioning
confidence: 99%